PERSEDIAAN PETIKEMAS EKSPOR PT. JARDINE SHIPPING SERVICE - Aswanti Setiawati; Titi Apriyanto (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2016)
PT. Jardine Shipping Service (JSS) is one of the shipping agency which acts as intermediary between goods’ delivery and ship operator companies. To find out the procedure of services and containers supply, to analyze the number of containers achieved based on the target, and to fulfill the containers availability, the researcher is using descriptive evaluative method. The result shows that the number of export containers’ availability in PT. JSS is 61 % based on the coming order and daily update which are informed by the containers’ depo of logistics division. Some efforts need to be done to fulfill the needs of containers which are borrowing from the same principal shipping agency and/or moving to the other principal which has the same purpose and containers’ availability.